(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This scientific article examines the crucial role of media in covering environmental issues. It explores the impact of media coverage on shaping public opinion, influencing policy decisions, and fostering environmental awareness. The article delves into various media formats, including print, television, radio, and digital platforms, to elucidate their unique contributions and challenges in covering environmental topics. Moreover, it explores the evolving landscape of environmental journalism in the era of rapid technological advancements and the importance of responsible and accurate reporting in addressing global environmental challenges.